SIMULASI PENGARUH PENGGUNAAN FILTER BUTTERWORTH PADA MASUKAN SINYAL GETARAN ACAK TERHADAP NILAI RATA-RATA MAGNITUDO - Orlando Farcend Ficdy Tumbelaka; Jotje Rantung; Michael Rembet (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2015)
ABSTRACT Filter in this research is interpreted as screening of undesirable frequency component. In this research, the highest different percentage of magnitude for the 15, 30, 45 until 150 times of excitation can be obtained. The impact excitation signal and the random excitation signal were develop using Matlab version 6.5. The random and impact signal then filtered using Butterworth filter. The excitation of random signal was develop using Matlab version 6.5. The simulation of random signal was proceed repeatedly over 15, 30, 45 until 150 times of excitation. The simulation resulted the average numbers of filter magnitude response. Which is then compared with the impact excitation signal indicated by percentage difference. Based on the results of simulation and calculation the maximum different percentage of highest magnitude occurred in the simulation of 15 times excitation (50%). The chart of the different percentage of highest magnitude tend to be flat at the 60 times until 150 times of excitation. While the average numbers of filter magnitude response due to the random signal excitation can not be considered as same as the numbers of filter magnitude response due to the impact signal, because the difference is above 5%. Keyword: Butterworth filter, random excitation signal, percentage difference of magnitude